Kinerja Operator dan Kehandalan Alat HMC Terhadap Produktivitas Bongkar Muat Curah Kering - Sumarzen Marzuki; Fransuskus Yanceanus Wair (Sekolah Tinggi Maritim Yogyakarta, 2020)
This study examines the influence of operator performance and the reliability of HMC tools on the productivity of dry bulk loading and unloading companies, the object of this study is PT. Peindo III Tanjung Perak Branch Jamrud Terminal Services Division. The research population was all 128 Jamrud Terminal operational employees. The number of samples drawn from a population of 56 people and this study uses quantitative methods and multiple linear regression analysis techniques. The results of the study stated that the operator performance and reliability of HMC equipment partially and simultaneously had a positive and significant effect on the productivity of the dry bulk loading and unloading at the Jamrud Terminal Service Division. If the performance of HMC operators increases, the productivity produced will increase and if the Harbor Mobile Crane (HMC) tool is more reliable the productivity will continue to be maximal and increase. The operator performance variable has the most influence compared to the reliability of the HMC tool.